How Do Fintech and Digital Banking Affect Indonesia Digital Bank Share Prices and Trading Volumes? - Jaya, Asri (Revenue Journal: Management and Entrepreneurship, 2024)
This research highlights the influence of Fintech and digital banking on the share prices and trading volumes of digital banks in Indonesia. It is an empirical study aimed at exploring the relationship between technological advancements in the financial sector and the performance of digital bank stocks. Through a comprehensive assessment of market data, the study investigates how innovations in Fintech and digital banking services impact investor behavior and market dynamics. The study employs a quantitative approach, analyzing data from various digital banks listed on the Indonesian stock exchange. The participants in this research include publicly traded digital banks with significant market capitalization and trading volumes. The data set spans over a period of five years, providing a robust basis for examining trends and patterns. This research reveals a notable gap in the literature regarding the direct effects of Fintech innovations on digital bank performance metrics, such as share prices and trading volumes. Moreover, the study identifies several deficiencies in the current market analysis frameworks, such as the lack of real-time data integration and the underestimation of Fintech's disruptive potential. To address these gaps, the research suggests the adoption of advanced analytics and real-time monitoring tools. The findings also indicate a significant increase in trading volumes and stock price volatility correlated with the introduction of new Fintech products and services. This underscores the critical role of technological innovation in shaping the future landscape of digital banking in Indonesia.